Mobilization of Arsenic with Iron, Manganese and Copper in Borehole Sediments of the River Jamuna - Rahman, Mohammad Arifur; Hasan, Md Mahmudul; Siddique, Nur-E-Alam; Alam, AM Shafiqul (Journal of the Bangladesh Chemical Society, 2012)
Boreholes sediments (to a depth of 1-6 m) from the Jamuna River area in Bangladesh were collected for arsenic concentration and geochemical analysis. Chemical analysis reveals that Mn and Fe hydroxides and organic matter are the major leachable solids carrying As. High levels of arsenic concentration in aquifers are associated with fine grained sediments. Moreover, it is clearly shows that As is closely associated with Fe and Mn in sediments. Arsenic mobilized in sediments with Fe, Mn and organic matter from upper stream to lower stream of the river Jamuna. There was no significant relationship observed between arsenic and Cu in borehole sediments. DOI: http://dx.doi.org/10.3329/jbcs.v25i1.11768 Journal of Bangladesh Chemical Society, Vol. 25(1), 30-37, 2011